NOVEL POLYTOPIC MACROCYCLIC RECEPTOR MOLECULES CONTAINING MULTIPLE BIPYRIDYL AND DIBENZO-18-CROWN-6 UNITS - Kocian, O; Mortimer, R; Beer, P (1990)
New polytopic macrocycles (7)-(11) containing multiple 4,4′-disubstituted-2,2′-bipyridyl and dibenzo-18-crown-6 units are described. Preliminary coordination studies reveal these novel ligands form polymetallic complexes with ruthenium and potassium guest cations. © 1990.